Observation of the B0s→X(3872)ϕ Decay - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen